Antisense oligonucleotide based therapeutics and its applications against bacterial infections - Nupur Angrish; Garima Khare (Elsevier, 2023)
The transcriptome of a cell governs the overall cellular expression of proteins, hence, targeting mRNA holds promise as a therapeutic strategy in the field of drug discovery. RNA therapeutics especially, antisense oligonucleotide (ASO) technology, have gained tremendous pace in the last few decades with many of the ASOs being evaluated in various clinical phases and several ASO-based drugs are currently marketed after FDA approval. Several chemical modifications in the nucleic acid backbone of ASOs have led to improved properties of ASOs, such as oligonucleotide stability, enhanced affinity, and better pharmacokinetics contributing to their therapeutic success. ASOs interfere with the translation process either by RNase H-mediated mRNA cleavage or by posing steric hindrance in the translation machinery. Further, the cellular delivery of ASOs has always remained questionable, however, with the advancements in the delivery approaches, it is now feasible to achieve better target specific cellular delivery. In this review, we provide comprehensive insights into antisense oligonucleotide therapeutics, their various modifications, the mechanisms involved, different strategies for their delivery, and the utility of ASOs against several bacterial diseases.